Evaluation of the Prevalence of Incidental Findings of Gynecological Diseases in Hip and Sacroiliac Magnetic Resonance Imaging (MRI) in a Tertiary Hospital in 2022 - Soleimantabar, Hussein; Goodarzi, Farid (Novelty in Biomedicine, 2024)
Background: Incidental findings in imaging are defined as findings that appear accidentally in radiological images, and usually, the patient does not have a complaint related to the desired finding. These findings range from no-risk to high-risk. This study aimed to evaluate the prevalence of incidental findings of gynecological diseases in hip and sacroiliac Magnetic Resonance Imaging (MRI) in Imam Hossein Hospital in 2022. Materials and Methods: In this cross-sectional descriptive study, all patients referred to Imam Hossein Hospital (Iran-Tehran) during one year (2022) who underwent hip and sacroiliac MRI were evaluated. Hip and sacroiliac MRI images were reviewed. The following pathological findings were recorded: pelvic vascular congestion, ovarian cyst, myoma, and ovarian masses. Patients' information about age and underlying disease were also extracted from patients' files. Hip and sacroiliac diseases were also recorded. Finally, all recorded data were analyzed using the SPSS program. Results: Hip and sacroiliac MRI of 364 female patients were assessed. The mean age of the patients was 50.18±13.46 years. Discopathy was the most prevalent finding in the MRI (41.76%) as a pathological finding. The prevalence of incidental findings was 32.3%. The most common incidental finding in MRI was free fluid with a prevalence of 12.1%, and ovarian cyst was seen in 6.3% of patients. There was a significant relationship between most of the incidental findings and age (P-values<0.05). Conclusion: The prevalence of incidental findings of gynecological diseases in women undergoing hip and sacroiliac MRI is considerable and shows the importance of the radiologist’s attention to review and report the entire MRI images.